The types of formality in legal transactions - E. Benelfakih (Юридичний часопис Національної академії внутрішніх справ)
The purpose of this study was to identify and distinguish the types of formality in legal transaction and to determine the legal consequences of each category’s absence from such transaction. For this reason, this study relied on both the analytical descriptive technique, which involved reviewing jurisprudence and legal provisions, and the comparative method, which involved conducting horizontal comparisons of legal texts. This study concluded that the sorts of formality were not limited neither by law nor jurisprudence. This fact has led to inconsistent judicial rulings in addition to conflicting legal ramifications. Furthermore, due to the nature of the procedures it represents, the study discovered that a new category of legal formalities is reflected in the electronic format, which is defined by some specific features. It was concluded that a series of legislative acts is moving towards formal transactions for protectionist and financial goals and objectives. Therefore, a clear distinction should be established between the types of formality, their limitation, and the effects of each type, so as to make it easier for the judiciary to set up suitable effects when some legal transactions lack the required formality. Electronic formality should also be considered by legally regulating it due to its features